36=3(x+9)

Simple and best practice solution for 36=3(x+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 36=3(x+9) equation:



36=3(x+9)
We move all terms to the left:
36-(3(x+9))=0
We calculate terms in parentheses: -(3(x+9)), so:
3(x+9)
We multiply parentheses
3x+27
Back to the equation:
-(3x+27)
We get rid of parentheses
-3x-27+36=0
We add all the numbers together, and all the variables
-3x+9=0
We move all terms containing x to the left, all other terms to the right
-3x=-9
x=-9/-3
x=+3

See similar equations:

| x.x+2=48 | | 3x-(7x+7)=-87 | | 6x/(9x+12)=0 | | S=17+y | | -2+5k=6k+2 | | -x+7(5x-23)=9 | | 8+2c=c-8+3c | | -x.x+1=48 | | 2^x=118 | | -12x+9(x+2)=6(x-6)+9 | | 2n+3=48 | | x.x-1=48 | | -(9x-15)=87 | | x.x+1=48 | | -2-3=8+9v | | x-0.2x=150 | | 3y-5+9y=7+9y | | -8-2(-8p+10)=10+7p-2 | | −3x2+12x−120=0 | | -10z-10=10-8z | | 7(4x-3)=-217 | | 400-2a=224 | | 6=x-2+10 | | 3(1+7a)=-81 | | -6(-4x+2)=-132 | | 200000=0.2*x | | 4(y–3)=-5y+51 | | 0.602=j-75 | | (5x*5x)+43=(x-1)(5x+6) | | 9x+3(52x)=15(x+1) | | m/42=-26 | | -5(1+5x)=-230 |

Equations solver categories